The Implementation of the Pancasila Student Profile Strengthening Project in Character Building - Azizah, Wafiq Nur; Rahmah, Eka Naelia (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2025)
This research is motivated by the decline in student character caused by the Distance Learning System (PJJ) during the Covid-19 pandemic. To address this issue, the Ministry of Education and Culture (Mendikbudristek) launched the Merdeka Curriculum along with its innovation, the Project Strengthening Pancasila Student Profile (P5). The purpose of this study is to analyze the implementation of P5 in shaping student character at MTsN 12 Jakarta. This research uses a descriptive qualitative approach with data collection methods including observation, interviews, and documentation. Data analysis is conducted through data collection, data reduction, data presentation, and conclusion drawing. The research findings indicate that the implementation of P5 involves three stages: planning, implementation, and evaluation. During the planning stage, the formation of the P5 facilitator team, school readiness assessment, design of dimensions, themes, and time allocation, as well as the preparation of modules and reporting strategies, were carried out. The implementation stage includes monitoring, optimization, and project closure activities. Evaluation is conducted through two-way discussions, observation, and the use of rubrics and questionnaires. The P5 activities have successfully shaped various student characters, such as being religious, nationalist, independent, cooperative, and having integrity, which are reflected in their daily activities.